A graph representation for search-based approaches to graph layout problems. (13th March 2020) - Koohestani, Behrooz
A graph consists of a finite set of vertices and edges. Graphs are used to represent a significant number of real life applications. For example, in computer science, graphs are employed for the representation of networks of communication, organisation of data, flow of computation, computational devices, etc. Several data structures have been proposed for representing graphs among which the adjacency matrix, adjacency list and edge list are the most important and widely used ones. The choice of a graph representation is mainly situation-specific and depends on the type of operations required to be performed on a given graph as well as the ease of use. In this research, a specialised graph representation is proposed, specifically designed for use when coping with graph-based optimisation problems (e.g., graph layout problems) through heuristic search methods with the aim of speeding up the search. The results of numerical experiments show that for the purpose of this study, the proposed approach performs extremely well compared to well-known graph representation approaches.